Near-infrared emissive lanthanide hybridized nanofibrillated cellulose nanopaper as ultraviolet filter. (15th April 2018) - Xue, Bailiang; Zhang, Zhao; Sun, Yongchang; Wang, Junjie; Jiang, Huie; Du, Min; Chi, Congcong; Li, Xinping
Highlights: The lanthanide complexes functionalized NFC nanopapers exhibit NIR luminescence. High transparency Ln-NFC nanopapers have high UVA and UVB block rate. NIR emission spectra of the Ln-NFC nanopapers were through the efficient triplet–triplet energy transfer process. Abstract: The lanthanide complexes [Yb(fac)3 (H2 O)2, Yb(tta)3 (H2 O)2, Nd(tta)3 (H2 O)2 ] functionalized nanofibrillated cellulose (Ln-NFC) nanopapers with near-infrared (NIR) luminescence and high transparency are rapidly fabricated after solvent exchange using a simple suction filtration film-making method. The effects of NFC and lanthanide complexes content on their photophysical properties of Ln-NFC nanopapers and their mechanism of UV filters are fully investigated. With increasing lanthanide complexes content in the Ln-NFC nanopaper, their transmittances are gradually decreased while their NIR luminescences are obviously increased. Yb-fac NFC nanopaper has high UVB block rate at 298 nm, whereas the high UVA block ratio of Ln-tta NFC nanopaper is observed at 345 nm. Ln-NFC nanopapers show a much higher photostability without decomposition under UV irradiation at 365 nm over 5 h. The emission spectra of the Ln-NFC nanopaper process the NIR luminescence of the corresponding lanthanide ions through the efficient triplet–triplet energy transfer process. Ln-NFC nanopapers can bring a brilliant future for UV filters, labeling fields and marking soft materials application.